# help rearranging this

• Oct 30th 2010, 02:43 PM
sugst893
help rearranging this
i am wanting to rearrange to make h the subject h the subject and then b the subject

S= √(b2-h2)

steve
• Oct 30th 2010, 02:50 PM
pickslides
Is your equation $S = \sqrt{b^2-h^2}$ ?

If so start by squaring both sides,

$S = \sqrt{b^2-h^2}$

$S^2 = b^2-h^2$

Then adding $h^2$ to both sides

$S^2+h^2 = b^2$

Finally taking the square root of both sides.

$\sqrt{S^2+h^2} = b$

$b = \sqrt{S^2+h^2}$

Do you follow?(Nod)
• Oct 30th 2010, 02:50 PM
mr fantastic
Quote:

Originally Posted by sugst893
i am wanting to rearrange to make h the subject h the subject and then b the subject

S= √(b2-h2)

steve

I assume it's meant to be $\displaystyle S = \sqrt{b^2 - h^2}$ .... (Use h^2 NOT h2 to repesent powers).

Start by squaring both sides, then make $h^2$ the subject etc.
• Oct 30th 2010, 03:19 PM
sugst893
Quote:

Originally Posted by pickslides
Is your equation $S = \sqrt{b^2-h^2}$ ?

If so start by squaring both sides,

$S = \sqrt{b^2-h^2}$

$S^2 = b^2-h^2$

Then adding $h^2$ to both sides

$S^2+h^2 = b^2$

Finally taking the square root of both sides.

$\sqrt{S^2+h^2} = b$

$b = \sqrt{S^2+h^2}$

Do you follow?(Nod)

that is great thankyou so much if i want h the subject id do the same but divide doth sides by b is that correct

thats so great
• Oct 30th 2010, 07:16 PM
mr fantastic
Quote:

Originally Posted by sugst893
that is great thankyou so much if i want h the subject id do the same but divide doth sides by b is that correct

thats so great

No. Post your working so that it can be reviewed.
• Oct 31st 2010, 12:10 PM
sugst893
ok so

first i would square both sides

then subtract s^2 from both sides

giving me h=sqrt{S^2-b^2}

stephen
• Oct 31st 2010, 12:22 PM
Unknown008
No, if you want to make it this way, it's a little different.

$S = \sqrt{b^2-h^2}$

Square both sides:

$S^2 = b^2-h^2$

Now, Move b^2;

$S^2 - b^2 = -h^2$

You see that there is a minus sign? Multiply both sides by -1:

$-S^2 + b^2 = h^2$

Rearrange:

$b^2 - S^2= h^2$

Now, you take the square root.

$\sqrt{b^2 - S^2}= h$

$h = \sqrt{b^2 - S^2}$